Prolonged exercise in hypoxia induces tissue-specific oxygenation profiles - Rupp, T.; Jubeau, M.; Wuyam, B.; Millet, G. Y.; Perrey, S.; Verges, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Tissue oxygenation, assessed by near-infrared spectroscopy, is altered during hypoxia at rest and during exercise (1). However, it remains still debated, depending on hypoxia severity and exercise characteristics, whether the tissue oxygenation perturbations are similar between sites especially within cerebral areas implicated in motor output (2). Also, it is unknown how far systemic arterial desaturation impacts muscle and cerebral oxygenation during exercise in hypoxia. The purpose of our study was to compare arterial and tissue oxygenation on multiple sites during prolonged submaximal cycling in hypoxia. Methods: Twelve healthy males completed three experimental conditions. After a 4-h wash-in period, either in normoxia (NE, FiO2=21%) or hypoxia (HE, FiO2=11%), subjects performed a 80-min cycling exercise at 45% of their maximal aerobic power. A 3rd control condition, in hypoxia, consisted on a 80-min resting period in which the arterial saturation (SpO2) reached during HE was matched by adjusting FiO2 (HR, FiO2.9%). Quadriceps, prefrontal (PFC) and motor cortices oxy[HbO2]- deoxy[HHb]- and total[THb]-haemoglobin concentration changes were continuously investigated using near-infrared sensors to assess tissue oxygenation status. Results: HR and HE resulted in similar SpO2 reduction (. - 20%). For the quadriceps, exercise-induced [Hbb] rises were associated with increased and unchanged [THb] in NE and HE, respectively, while [THb] dropped significantly in HR. PFC showed a large [THb] increase at exercise with a four-fold [HbO2] increase compared to [HHb] in NE versus a four-fold [Hbb] increase compared to [HbO2] in HE. Motor cortex showed similar [HbO2] decrease and [HHb] increase than PFC in HR but not at exercise. Indeed, motor cortex [THb] was stable in HE and NE while [HbO2] decreased and [HHb] increased in NE, these latter changes being significantly accentuated in HE. Discussion: This study quantifies for the first time the respective effects of prolonged cycling exercise and systemic arterial desaturation in muscle and cerebral oxygenation responses in hypoxia. These results demonstrate that specific responses to prolonged exercise and/or hypoxia are found between tissues and between cortical sites implicated in physical exercise, as shown by concomitant CPF hyperoxygenation and motor cortex deoxygenation in NE